Treatment of Shrimp Pond Effluent using Sedimentation Pond in the Tropics - Ling, Teck Yee; Nyanti, L.; George, B. (David Publishing, 2011)
Aquaculture plays a major role in providing the needed protein. However, there have been reports of negative impacts of shrimp farming which include environmental pollution. Therefore, shrimp pond effluent had to be retained for treatment. Treatment in tanks showed good improvement in water quality but in sedimentation ponds it may not be the case. Therefore, the objective of this study was to determine the water quality of effluent retained in sedimentation pond for a duration of76 hours. Results show that water quality at 113 depth was better than 2/3 depth. There was an improvement in water quality with reductions of TSS, BODs, COD,nitrate-N, nitrite-N, SRP and TP ranging from 25-52% except for DO and TAN. In addition, there was fluctuation of each parameter during the duration of study. It is important to monitor the water quality prior to the release of effluent so that it coincides with low nutrients and acceptable DO and partial release ofthe top 1/3 portion is recommended. There is a limit on the reduction achievable by sedimentation ponds likely due to processes occurring in the sediment. For higher reductions, other methods of effluent management and recovery of nutrients have to be considered.